Pengaruh Kualitas Layanan dan Fasilitas Perpustakaan terhadap Kepuasan Siswa di SDN Balongsari 1/500 Surabaya - Fitria Jannah Istiqomah (Jurnal Riset dan Inovasi Manajemen, 2025)
This study aims to analyze the effect of service quality and library facilities on student satisfaction at SDN Balongsari I/500 Surabaya. The quality of library services includes aspects of speed, reliability, and responsiveness of library staff, while library facilities include the availability of book collections, reading rooms, and other supporting facilities. The research method used is quantitative with a survey approach. The research sample consisted of 85 students who actively use the library at SDN Balongsari I/500 Surabaya, who were selected by proportional stratified random sampling. Data were collected through questionnaires and analyzed using multiple linear regression to test the effect of service quality and facility variables on student satisfaction. The results showed that the quality of library services and facilities simultaneously, as indicated by the calculated F value greater than the F table value, namely the calculated F of 8.094 and the F table of 3.9574, had a positive and significant effect on student satisfaction. Partially, the calculated t value for the service quality variable was 4.898 while the calculated T value for the facility variable was 4.850. So service quality has a more dominant influence than library facilities. This study suggests improving service quality and developing library facilities as a strategy to increase student satisfaction in utilizing school libraries. Keywords: Quality of Library Services and Facilities and Student Satisfaction.